Squamous cell carcinoma in mare – Case report - Lima, Artur Ângelo Rodrigues de (2022)
It is reported a squamous cell carcinoma (CCE) located in the vulva of a female 12-year-old crossbreed horse, raised in an extensive system. The mare presented a granulomatous tumour adhered to the vulva, which had progressive growth and affected the entire area of the vulva. The tumour showed a whitish red colour, solid consistency, non-regular surface and ulcerations. The diagnosis was made using the histopathological technique using three fragments and had a compatible result for squamous cell carcinoma.